2022
DOI: 10.3390/ijms23031879
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Metabolome in Parkinson’s Disease and Multiple System Atrophy

Abstract: Parkinson’s disease (PD) and multiple system atrophy (MSA) belong to the neurodegenerative group of synucleinopathies; differential diagnosis between PD and MSA is difficult, especially at early stages, owing to their clinical and biological similarities. Thus, there is a pressing need to identify metabolic biomarkers for these diseases. The metabolic profile of the cerebrospinal fluid (CSF) is reported to be altered in PD and MSA; however, the altered metabolites remain unclear. We created a single network wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 117 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…Through microarray analysis on substantia nigra tissue, heat shock protein HSPA1A and HSPA1B were found to be upregulated in PD, indicating that this may be a common response to attenuate the adverse effects of misfolded protein 112 . ECM1 was also shown to be upregulated in the CSF samples of PD patients 113 . Interestingly, one of the most common genetic risk factors for PD is having a mutated GBA gene 114 .…”
Section: Discussionmentioning
confidence: 95%
“…Through microarray analysis on substantia nigra tissue, heat shock protein HSPA1A and HSPA1B were found to be upregulated in PD, indicating that this may be a common response to attenuate the adverse effects of misfolded protein 112 . ECM1 was also shown to be upregulated in the CSF samples of PD patients 113 . Interestingly, one of the most common genetic risk factors for PD is having a mutated GBA gene 114 .…”
Section: Discussionmentioning
confidence: 95%
“… di Biase et al (2020) review reported an accuracy of over 0.83 for PD diagnosis using ML based on gait feature testing. Kwon et al (2022) review demonstrated that the integration of clinically relevant biomarkers such as metabolomics, proteomics, and microRNA omics data from cerebrospinal fluid can serve as a powerful method for identifying PD and MSA. The aforementioned research results demonstrate that diagnostic models based on different variables have good performance in PD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the exploration of candidate biomarkers for MSA, disregarding its close relationship with PD does not seem justifiable. Several recent studies have shown that SYN might be a potential diagnostic biomarker for PD in CSF though the results are inconsistent [57][58][59]. The results of a meta-analysis investigating the diagnostic and differential diagnosis efficacy of CSF SYN in PD have shown that its median concentration is significantly lower in PD compared to controls, but significantly higher in PD as compared to MSA [60,61].…”
Section: Syn and Tppp As Biomarkersmentioning
confidence: 99%